2023
DOI: 10.1371/journal.pone.0280202
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of muscle ultrasound in appendicular skeletal muscle mass estimation for sarcopenia assessment

Abstract: The measurement of skeletal muscle mass is essential for the diagnosis of sarcopenia. Muscle ultrasonography has emerged as a useful tool for evaluating sarcopenia because it can be used to assess muscle quality and quantity. This study investigated whether muscle ultrasonography is effective for estimating appendicular skeletal muscle mass (ASM) and screening for sarcopenia. This study prospectively enrolled 212 healthy volunteers aged 40–80 years. ASM was measured using the bioelectrical impedance analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Moreover, investigators have demonstrated the relationship between muscle strength and muscle cross-sectional area [ 24 ]. US has been increasingly used as a tool to measure muscle mass-related indicators [ 9 , 16 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. The muscle thickness measured by US is closely related to the cross-sectional area measured by both US and computed tomography [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, investigators have demonstrated the relationship between muscle strength and muscle cross-sectional area [ 24 ]. US has been increasingly used as a tool to measure muscle mass-related indicators [ 9 , 16 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. The muscle thickness measured by US is closely related to the cross-sectional area measured by both US and computed tomography [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, if used with standardized techniques to minimize potential limitations, a hand-held dynamometer can establish reliability and validity [ 49 , 50 ]. Finally, we used the linear regression model to develop an ASM prediction equation, which was the statistical method used in the previous studies [ 9 , 16 , 51 , 52 , 53 ] with similar study objects. However, caution should be applied in the interpretation of the final result.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The golden years, as always, spawn their own issues, with sarcopenia and gradual muscle mass and function loss being the leading ones [53]. Ultrasonography using a feature that provides with muscle mass and quality assessment becomes an unreplaceable tool in detecting age-related pathology [54]. The ultrasonography method that includes the assessment of body areas, such as muscle thickness, area of crosssection, and intramuscular fat concentration, provides a comprehensive picture on the structural changes due to age and helps to define the influence of age on muscle alterations [55].…”
Section: Imaging Muscle Inflammation Across the Lifespanmentioning
confidence: 99%
“…Later, the participants lie supine with their limbs extended and relaxed (Li et al, 2020). The muscle thickness was measured in the short-axis view at the maximal vertical distance from the superficial to deep fascia layers (Baek et al, 2023). The assessment commences using the portable handheld Linear Series UProbe-L5 for the initial three muscle thickness measurements, followed by three additional measurements utilizing the Hitachi Aloka F37 ultrasound machine.…”
Section: Study Organizationmentioning
confidence: 99%